Nilai Interaksi Simbol Tradisi dalam Wujud Pelinggih pada Ruang Publik - Julianto, I Nyoman Larry; Jodog, Made; Santoso, Imam (PANGGUNG, 2016)
ABSTRACTÃÂ In public space in North Bali, there has been concept ÃÂ change ÃÂ of symbol tradition ÃÂ visualiza- tion in the form of pelinggih ÃÂ which is in the form ÃÂ of car. But its essential function as a placeÃÂ  of worship has not changed. The surrounding ÃÂ community ÃÂ can accept that phenomenon as adop- tion process and identity ÃÂ of cultural heritage.Through qualitative ÃÂ research, try to be understood ÃÂ a Ã¢â¬Ëcreative ÃÂ processÃ¢â¬â¢ outside Ã¢â¬Ëcontext ÃÂ of the selfÃ¢â¬â¢ in communicating ÃÂ the message through ÃÂ visual media. From this research stated that visual form of pelinggih ÃÂ not only the expression result of beauty, ÃÂ but also to communicate ÃÂ the message. Ritual principles ÃÂ of a pelinggih is still maintained.ÃÂ  Its materialization ÃÂ concept has undergonenovelty ÃÂ identity ÃÂ due to unification ÃÂ of aesthetic ÃÂ value, art, spiritual and Ã¢â¬Ëmoderniza- tionÃ¢â¬â¢ in the context ÃÂ of Ã¢â¬ËworldlyÃ¢â¬â¢ ÃÂ life. SymbolÃÂ  visualization ÃÂ in an effort to communicate ÃÂ that message, ÃÂ contains ÃÂ elements ÃÂ of cultural system ÃÂ acculturationÃÂ  ÃÂ of todayÃ¢â¬â¢s society to mutually ÃÂ in- teract.ÃÂ Keywords: symbol tradition, ÃÂ visual change, ÃÂ identity ÃÂ of novelty, ÃÂ public ÃÂ spaceÃÂ  ABSTRAKÃÂ Pada ruang publik di Bali Utara, terjadi perubahan konsep visualisasi simbol tradisi dalam wujud pelinggih, yakni berbentuk mobil. Fungsi esensinya sebagai tempat pemujaan tidak berubah. Masyarakat sekitar dapat menerima fenomena tersebut sebagai proses adopsi dan identitas warisan budaya.Melalui penelitian kualitatif, berupaya dipahami sebuah Ã¢â¬Ëproses kreatifÃ¢â¬â¢ diluar Ã¢â¬Ëkonteks diriÃ¢â¬â¢ dalam mengomunikasikan pesan melalui media visual. Dari penelitian ini, dinyatakan bahwa wujud visual pelinggih tidak hanya hasil ekspresi keindahan, tetapi juga mengomunikasikan pesan. PrinsipÃ¢â¬âprinsip ritual sebuah pelinggih tetap dipertahankan. Konsep perwujudannya mengalami identitas kebaruan akibat dari penyatuan nilai estetis, seni, spiritual serta Ã¢â¬ËmodernisasiÃ¢â¬â¢ dalam konteks kehidupan Ã¢â¬ËduniawiÃ¢â¬â¢. Visualisasi simbol dalam upaya mengomunikasikan pesan tersebut, mengandung unsurÃ¢â¬âunsur akulturasi sistem budaya masyarakat masa kini untuk saling berinteraksi.ÃÂ Kata kunci : simbol tradisi, perubahan visual, identitas kebaruan, ruang publik